Hymenasplenium hastifolium sp. nov. (Aspleniaceae) from a karst cave in western Guangxi, China - Xu, Ke-Wang; Zhou, Xin-Mao; Zhang, Li-Bing; Liao, Wen-Bo (Phytotaxa, 2018)
A new fern species, Hymenasplenium hastifolium (Aspleniaceae), from a limestone cave in western Guangxi, China, is described and illustrated. Morphological affinities of genus Hymenasplenium are also compared and discussed. The new species is distinguished by the shape of lamina, the venation, and the sorus distribution. Hymenasplenium hastifolium was found at a cave entrance and is currently known only from one population with ca. 50 individuals. It should be classified as Critically Endangered (CR) following IUCN Red List criteria.